Dinamika Kesejahteraan Jiwa Dalam Praktik Self Healing Perspektif Tafsir Al-Maraghi - Nisa’, Zakiyatun; Masrury, Farhan (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The implications of the Qur'an on mental health are evident in its role in human life. Mental health entails freedom from psychological disorders, the traumas often encountered, and maintaining mental function balance and self-perception. This study aims to investigate the dynamics of mental well-being in the practice of self healing from the perspective of al-Maraghi's interpretation, particularly amidst rapid social and technological advancements. The research employs a Library Research approach with a thematic interpretation. The findings highlight the significance of spiritual awareness, moral values, and self-reflection emphasized in the Qur'an for mental well-being. Additionally, social support plays a crucial role in maintaining mental health, underscoring the importance of positive relationships and virtuous behavior in achieving inner peace. The study emphasizes the integration of spiritual, psychological, and social dimensions for inner harmony.